Humanising healthcare spaces through culture: designing of labour delivery room for the Malay Muslim community as case study - Mohd Nawawi, Norwina; Abdul Rahim, Zaiton (Tesis-Inter University Research Centre, 2016)
Modern an women had lived in medicalised world from birth till death with the advent of modern sciences brought about into the healthcare environment. Culture as a way of life of ordinary man suddenly stops as one enters the alien world of modern healthcare where certain expected behavioral standards are required. Many researches were made to humanises healthcare environment so as to soften the clashes of the environment.However, there are very little inroads made to humanise the clinical areas of the healthcare environment apart from interior decoration and spatial layout. Malaysia had awaken from its colonial days and accepted the fact that traditional medicines lives in a separate stream from the mainstream modern medicine as alternative choices.Birthing as a normal event, however has been brought modern healthcare from its traditional setting to save life of both mother and child. The objective of this research is to humanise the clinical spaces of the modern healthcare environment using labour delivery room as the case study and the Malay-Muslim culture as the humanising factor